Does the decline in road traffic injury in London vary by ethnicity?. Issue 5 (3rd October 2008) - Malhotra, N; Hutchings, A; Edwards, P
Abstract : Objective: To examine ethnic variations in trends in road traffic injuries in London. Design: Analysis of STATS19 data comparing trends in road traffic casualty rates by ethnic group. Setting: London, 2001–6. Subjects: Children (⩽14 years) and adults (⩾15 years). Main outcome measures: Annual casualty rates in white, black, and Asian pedestrians, cyclists, and car occupants. Results: Casualty rates in London declined each year between 2001 and 2006 by an average of 8.8% (95% CI 8.5% to 9.0%). After adjustment for area-level deprivation, there was good evidence that the average annual reduction in injury rates in car occupants was significantly less in Asian than in white adults (10.9% vs 14.4%, p<0.001). There was some evidence that average annual reductions in injury rates were lower in black than in white adult pedestrians (7.4% vs 9.3%, p = 0.041) and car occupants (13.2% vs 14.4%, p = 0.03). Conclusions: Casualty rates in London have declined for pedestrians, cyclists, and car occupants in three broad ethnic groups. Asian car drivers appear to have benefited least from these reductions.